2020
DOI: 10.1038/s41598-020-73693-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrojet-based delivery of footprint-free iPSC-derived cardiomyocytes into porcine myocardium

Abstract: The reprogramming of patient´s somatic cells into induced pluripotent stem cells (iPSCs) and the consecutive differentiation into cardiomyocytes enables new options for the treatment of infarcted myocardium. In this study, the applicability of a hydrojet-based method to deliver footprint-free iPSC-derived cardiomyocytes into the myocardium was analyzed. A new hydrojet system enabling a rapid and accurate change between high tissue penetration pressures and low cell injection pressures was developed. Iron oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Whether the stem cells are injected using intracoronary (IC) or intramyocardial (IM), the localization of stem cells is a problem to be solved. Weber et al 32 described a hydrojet-based technique to transplant cardiomyocytes which derived from footprint-free induced pluripotent stem cells (iPSCs) into myocardium. As a more precise and less invasive way to transplant stem cells, hydrojet-based technique has the potential to be a superior approach to traditional needle-based injections (eg, IC or IM) in future CABG procedures or other cell-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the stem cells are injected using intracoronary (IC) or intramyocardial (IM), the localization of stem cells is a problem to be solved. Weber et al 32 described a hydrojet-based technique to transplant cardiomyocytes which derived from footprint-free induced pluripotent stem cells (iPSCs) into myocardium. As a more precise and less invasive way to transplant stem cells, hydrojet-based technique has the potential to be a superior approach to traditional needle-based injections (eg, IC or IM) in future CABG procedures or other cell-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also begun to develop techniques for transdifferentiating fibroblasts directly into cardiomyocytes ( Sadahiro 2019 ), which suggests that endogenous cardiac fibroblasts could be a viable target for regenerative myocardial therapy, but the efficiency of the transdifferentiation procedure is exceptionally low. Thus, the transplantation of cardiomyocytes differentiated from human embryonic stem cells or, especially, hiPSCs ( Romagnuolo et al, 2019 ; Sadahiro 2019 ; Yoshida et al, 2020 ) continues to be among the most promising strategies for regenerative myocardial therapy ( Yoshida and Yamanaka 2017 ; Samak and Hinkel 2019 ; Weber et al, 2020 ). Nevertheless, despite substantial evidence that hiPSC-CMs tend to more closely resemble fetal cardiomyocytes than the cardiomyocytes of adult animals ( Robertson, Tran, and George 2013 ), their intrinsic cell-cycle activity remains limited and, consequently, the small number of transplanted hiPSC-CMs that are typically retained and survive at the site of administration cannot substantially remuscularize the myocardial scar ( Isomi, Sadahiro, and Ieda 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For WJ injections of pADSCs, vital cell yields of 84.7% and 74.8% were reported for WJ and WN, respectively [ 12 ]. Another study demonstrated no significant difference between WN and WJ (both about 95%) [ 17 ]. This demonstrates a high reproducibility of a standardized injection protocol as is realized by WJ compared to needle injections, where the outcome is dependent on the size of the syringe and needle, the pressure of the syringe, flow rate, and the physician who executes the injection itself.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented and validated by our study focused primarily on in vitro investigations that pave the way for future in vivo studies. Future research efforts will focus on not only addressing SUI [12,18] but also on other forms of incontinence and pathologies such as heart attack [17]. Overall, the WJ technology satisfies several key considerations required in a clinical context, such as the ease of loading and use, reproducibility of delivery, and precise delivery of viable cells under guided visual control.…”
Section: Discussionmentioning
confidence: 99%